Tumor-derived ILT4 induces T cell senescence and suppresses tumor immunity. Issue 3 (2nd March 2021) - Gao, Aiqin; Liu, Xia; Lin, Wenli; Wang, Jingnan; Wang, Shuyun; Si, Fusheng; Huang, Lan; Zhao, Yangjing; Sun, Yuping; Peng, Guangyong
Abstract : Background: Current immunotherapies including checkpoint blockade therapy have limited success rates in certain types of cancers. Identification of alternative checkpoint molecules for the development of effective strategies for tumor immunotherapy is urgently needed. Immunoglobulin-like transcript 4 (ILT4) is an immunosuppressive molecule expressed in both myeloid innate cells and malignant tumor cells. However, the role of tumor-derived ILT4 in regulating cancer biology and tumor immunity remains unclear. Methods: ILT4 expression in tumor cells and patient samples was determined by real-time PCR, flow cytometry, and immunohistochemistry. T cell senescence induced by tumor was evaluated using multiple markers and assays. Moreover, metabolic enzyme and signaling molecule expression and lipid droplets in tumor cells were determined using real-time PCR, western blot and oil red O staining, respectively. Loss-of-function and gain-of-function strategies were used to identify the causative role of ILT4 in tumor-induced T cell senescence. In addition, breast cancer and melanoma mouse tumor models were performed to demonstrate the role of ILT4 as a checkpoint molecule for tumor immunotherapy. Results: We reported that ILT4 is highly expressed in human tumor cells and tissues, which is negatively associated with clinical outcomes. Furthermore, tumor-derived ILT4/PIR-B (ILT4 ortholog in mouse) is directly involved in induction of cell senescence in naïve/effector T cells mediated by tumor cells in vitro and in vivo. Mechanistically, ILT4/PIR-B increases fatty acid synthesis and lipid accumulation in tumor cells via activation of MAPK ERK1/2 signaling, resulting in promotion of tumor growth and progression, and induction of effector T cell senescence. In addition, blocking tumor-derived PIR-B can reprogram tumor metabolism, prevent senescence development in tumor-specific T cells, and enhance antitumor immunity in both breast cancer and melanoma mouse models. Conclusions: These studies identify a novel mechanism responsible for ILT4-mediated immune suppression in the tumor microenvironment, and prove a novel concept of ILT4 as a critical checkpoint molecule for tumor immunotherapy.